Comparing Efficiency and Productivity in Islamic Banking : Case Study Indonesia, Malaysia and Pakistan - Rodoni, Ahmad; Salim, M. Arskal; Amalia, Euis; Rakhmadi, Rezki Syahri (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2017)
The objective of this research is to analyze both efficiency and productivity of  Islamic Banking Industry in Indonesia, Malaysia and Pakistan. The technique that used in this research is Data Envelopment Analysis (DEA) as for measuring efficiency and thus Malmquist Index (MI) as for measuring productivity. The result of this research found that Islamic Banking Industry in Indonesia is facing inefficiency that shown by five years average that is not reach 100% efficiency rate. Malaysia also experiences the problem of inefficiency but the condition is better compared to Indonesia. In five years, the efficiency rate of Malaysia Islamic Bank has not reach 100% efficiency rate. Pakistan among the closest country that could reach an efficient rate level for their Islamic banks. Pakistan close to reach 100% efficient rate within the last five years. DOI: 10.15408/aiq.v9i2.5153